Noblista w ogniu krytyki. Sienkiewicz – dzisiaj (i wczoraj) - Trybuś, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
The works of Henryk Sienkiewicz, the first Polish Nobel Prize winner, awarded for literature in 1905, have been and still are broadly resonating. The author of Quo vadis and Trylogia (The Trilogy) – “der Liebling der Massen” – is the victim of his own success as the popularity of literature reduces its meanings, it creates and then replicates the stereotypes in their reading. Sienkiewicz, a Catholic writer who represented Poland in his Trilogy as “the bulwark of Christianity” was always a convenient tool for shaping conservative attitudes. The article focuses on the reception of Sienkiewicz’s works at the end of the rule of Zjednoczona Prawica (the United Right) in Poland (2015–2023). It recalls, among others, the 2019 book Sienkiewicz z nami (Sienkiewicz with us), written by the writer’s great-grandson and politician Bartłomiej Sienkiewicz, part of which is the project aimed at deconstructing the right-wing reception of Henryk Sienkiewicz’s works. The author of the article also refers to earlier evidence concerning their reception over the course of the 20th century. The focus is on the texts which were accusatory and rejecting towards them, published ever since they became widely-read (opinions by S. Brzozowski and W. Gombrowicz, among others), as well as those written by past and contemporary experts in Sienkiewicz’s writings.